Empirical relationship between detection thresholds and physical parameters of different Nuclear Track Detectors - Bhattacharyya, Rupamoy; Dey, S.; Ghosh, Sanjay K.; Maulik, A.; Raha, Sibaji; Syam, D. (Perspectives in science, 2019)
The relationship between different physical parameters of various polymers (e.g., CR-39, Lexan, and PET) used as Nuclear Track Detectors (NTDs) and their intrinsic detection thresholds were investigated. A strong correlation was found between the electrical resistivity and detection thresholds of the NTDs and from that an empirical relationship between the two established. The predicted value of the detection threshold for Perspex® obtained from that empirical formula is in good agreement with its experimentally determined value.